HISTÓRIA NATURAL DA ESTENOSE AÓRTICA DEGENERATIVA: UMA REVISÃO SISTEMÁTICA DO CURSO DA DOENÇA E DOS PREDICTORES DE PROGRESSÃO - Vardasca, Gustavo Henrique de Moura; de Campos, Eduardo Coviello Mendes (LUMEN ET VIRTUS, 2025)
Introduction: Degenerative aortic stenosis (AS) is the most common valvular disease in aging populations, characterized by progressive calcification and narrowing of the aortic valve leading to left ventricular overload and heart failure. Understanding the natural history and predictors of disease progression is critical for optimizing timing of intervention and patient follow-up. Objective: The main objective of this systematic review was to evaluate the natural course of degenerative AS and identify clinical, echocardiographic, and biochemical predictors of progression. Secondary objectives included assessing annual changes in hemodynamic parameters, incidence of adverse cardiac outcomes, and impact of comorbidities on disease acceleration. Methods: A systematic search was performed in PubMed, Scopus, Web of Science, Cochrane Library, LILACS, ClinicalTrials.gov, and ICTRP. Observational and interventional studies published in the last 5 years were included, with extension to 10 years if fewer than 10 eligible studies were available. Two independent reviewers screened titles and abstracts, extracted data, and assessed bias using RoB 2, ROBINS-I, or QUADAS-2 as appropriate. Certainty of evidence was graded using GRADE. Results and Discussion: 27 studies met inclusion criteria. Most cohorts demonstrated a nonlinear yet measurable progression of valve calcification and gradient increase over time. Elevated baseline aortic jet velocity, lipoprotein(a), and valvular calcium scores were consistent predictors of faster progression. The pooled annual increase in mean gradient ranged between 4–8 mmHg, and event-free survival declined significantly once peak velocity exceeded 4.0 m/s. Conclusion: Degenerative AS is a dynamic and heterogeneous condition influenced by metabolic, inflammatory, and structural mechanisms. Early identification of high-risk phenotypes may guide timely valve replacement and improve outcomes.